2022
DOI: 10.1002/jeq2.20406
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microbial communities in soil treated with organic or conventional N sources

Abstract: Despite the extensive use of N fertilizers in agricultural soils, we are yet to fully understand their impact on soil microbial communities that mediate important soil processes. A 3-yr field study was undertaken in Georgia, where sweet corn (Zea mays L.) was grown under conventional or organic systems. Nitrogen (N) was supplied with ammonium sulfate at 112 kg N ha -1 (AS100) or 224 kg N ha -1 (AS200) or a combination of poultry litter, cover crop, and blood meal at 112 kg N ha -1 (PL100) or no N (control). So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The soil microbial community properties and diversity might be strongly influenced by soil physical and chemical properties, such as soil moisture and soil nutrient availability, and could reflect changes in soil ecological processes ( Habteselassie et al, 2022 ; Li et al, 2022 ). This study showed that preceding crop cultivation could significantly affect the physicochemical properties of tobacco-plant soil, overall depends on the crop types.…”
Section: Discussionmentioning
confidence: 99%
“…The soil microbial community properties and diversity might be strongly influenced by soil physical and chemical properties, such as soil moisture and soil nutrient availability, and could reflect changes in soil ecological processes ( Habteselassie et al, 2022 ; Li et al, 2022 ). This study showed that preceding crop cultivation could significantly affect the physicochemical properties of tobacco-plant soil, overall depends on the crop types.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, total viable aerobic (TVA) counts were higher in organic than conventional at both sampling times, whereas anaerobic microbial counts were higher in organic only at T1 and for oligotrophs only at T2. Higher levels of microorganism diversity are usually reported in organic farming due to the higher amount of organic matter [49]. Additionally, shifts over time in microbial communities are common [50].…”
Section: The Farming System Conditions the Status Of The Soilmentioning
confidence: 99%